Digitalization in urban planning: how Europe is building its digital future - D'Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban strategies, programmers and tools section presents presents the different strategies and tools that guide the digitalization of urban planning. This contribution aims to provide an overview of the policy tools employed by the European Union for digital transformation, and how they apply specifically to the governance of urban and territorial transformations. Digital transformation is a complex and ongoing undertaking, and the EU is mobilizing a range of tools to shape its digital future. Some of the key levers of this strategy are examined, including the Digital Decade Policy Programme (DDPP), financial instruments such as the Recovery and Resilience Facility (RRF) and the Digital Europe Programme (DIGITAL), and the INSPIRE regulatory instrument.